Identification of Multiple Substrates of the StkP Ser/Thr Protein Kinase in Streptococcus pneumoniae - Nováková, Linda (American Society for Microbiology (ASM), 2010)
Monitoring the external environment and responding to its changes are essential for the survival of all living organisms. The transmission of extracellular signals in prokaryotes is mediated mainly by two-component systems. In addition, genomic analyses have revealed that many bacteria contain eukaryotic-type Ser/Thr protein kinases. The human pathogen Streptococcus pneumoniae encodes 13 two-component systems and has a single copy of a eukaryotic-like Ser/Thr protein kinase gene designated stkP. Previous studies demonstrated the pleiotropic role of the transmembrane protein kinase StkP in pneumococcal physiology. StkP regulates virulence, competence, and stress resistance and plays a role in the regulation of gene expression. To determine the intracellular signaling pathways controlled by StkP, we used a proteomic approach for identification of its substrates. We detected six proteins phosphorylated on threonine by StkP continuously during growth. We identified three new substrates of StkP: the Mn-dependent inorganic pyrophosphatase PpaC, the hypothetical protein spr0334, and the cell division protein DivIVA. Contrary to the results of a previous study, we did not confirm that the α-subunit of RNA polymerase is a target of StkP. We showed that StkP activation and substrate recognition depend on the presence of a peptidoglycan-binding domain comprising four extracellular penicillin-binding protein- and Ser/Thr kinase-associated domain (PASTA domain) repeats. We found that StkP is regulated in a growth-dependent manner and likely senses intracellular peptidoglycan subunits present in the cell division septa. In addition, stkP inactivation results in cell division defects. Thus, the data presented here suggest that StkP plays an important role in the regulation of cell division in pneumococcus.